Evaluation of Serum Concentration of the Myokine Irisin (FNDC5) in Patients with Age-Related Macular Degeneration - Turgut, Burak; Mercan, Kadir; Ilhan, Nevin; Aydoğan, Selahattin Semih (My University, 2021)
Objectives: This study evaluated the serum irisin level of patients with age-related macular degeneration (ARMD) and compared it with that of healthy individuals. Methods: The serum irisin level of 15 healthy controls (Group 1) and 15 dry ARMD patients (Group 2) and 15 wet ARMD patients (Group 3) were measured using the enzyme-linked immunosorbent assay (ELISA) method and compared. Results: There was no statistically significant difference between the groups in terms of age or gender (p>0.05). The mean serum irisin levels of Group 1, Group 2, and Group 3 were 25.81±24.04 ng/mL, 22.93±19.05 ng/mL, and 12.38±8.16 ng/mL, respectively. Although the mean irisin level in the wet ARMD patients was lower than that of the control and dry ARMD groups, there was no statistically significant difference between the groups (p>0.05). Conclusion: The results suggest that the serum irisin level in ARMD patients is not different from that of healthy individuals. Studies of larger groups that examine the irisin level in the vitreous and neovascular membranes will further elucidate any role in the pathogenesis of ARMD.
Keywords: Göz Hastalıkları